1988
DOI: 10.1080/00014788.1988.9729371
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Accounting Information in Valuing Unlisted Shares

Abstract: Little research has been conducted on how professional accountants value unlisted shares. The study reported in this paper analyses the accounting and other data drawn from 185 actual unlisted share valuation reports within seven major Canadian accounting firms to estimate a model of and to explain variations in the values placed on unlisted shares.The findings suggest that valuation of unlisted shares can be explained largely in terms of historic accounting data, the main sources being earnings, earnings stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In that regard, Desai, Roberts, and Srivastava () report that IA objectivity, competence, and work performance are interdependent, such that EAs' judgments of the IAs remain high even if one of these factors is evaluated negatively; thus, further empirical verification is needed. Moreover, auditors seem to have relatively high levels of self‐insight (Ashton, ; Gibbins & Swieringa, ; Solomon & Shields, ) as a result of the audit profession's auditing standards and consistency in auditor training (Libby, ; Pike, Sharp, & Kantor, ). It is important to gauge the level of self‐insight so as to improve understanding of the learning process (Libby, ) and improve the accuracy of judgment (Hooper & Trotman, ).…”
Section: Introductionmentioning
confidence: 99%
“…In that regard, Desai, Roberts, and Srivastava () report that IA objectivity, competence, and work performance are interdependent, such that EAs' judgments of the IAs remain high even if one of these factors is evaluated negatively; thus, further empirical verification is needed. Moreover, auditors seem to have relatively high levels of self‐insight (Ashton, ; Gibbins & Swieringa, ; Solomon & Shields, ) as a result of the audit profession's auditing standards and consistency in auditor training (Libby, ; Pike, Sharp, & Kantor, ). It is important to gauge the level of self‐insight so as to improve understanding of the learning process (Libby, ) and improve the accuracy of judgment (Hooper & Trotman, ).…”
Section: Introductionmentioning
confidence: 99%
“…The next area of publications is discussing the difference in financial market data and accounting data. The oldest article on «financial data vs accounting data» (Pike et al, 1988) analysed the accounting and other data drawn from 185 actual unlisted share valuation reports within seven major Canadian accounting firms. It was to estimate a model of and to explain variations in the values placed on unlisted shares and found that valuation of unlisted shares can be explained largely in terms of historical accounting data, the main sources being earnings, earnings stability and asset book value.…”
mentioning
confidence: 99%